METABOLIC REGULATION AND EPIGENETIC CONTROL: UNRAVELING THE COMPLEXITY OF SKELETAL STEM CELL FATE AND BONE HEALTH - Wahyuni, Afrinda Dwi (Journal of Stem Cell Research and Tissue Engineering, 2024)
Skeletal stem cells (SSCs) are essential for bone formation and tissue regeneration within the skeletal system. These self-regenerating cells differentiate into various skeletal cell types, maintaining skeletal health. However, aging diminishes SSC capacity, impacting skeletal integrity. Epigenetics, the study of heritable changes in gene expression, plays a crucial role in stem cell regulation. Mechanisms like DNA methylation and histone modifications control gene expression without altering the DNA sequence. Dysregulation of epigenetic processes in transplanted cells may lead to immunological rejection or functional impairment. Understanding epigenetic regulation in stem cells is vital for tissue regeneration strategies. This narrative review focuses on summarizing existing scientific literature on epigenetic regulation within stem cells, particularly skeletal stem cells. The study utilized Google Scholar to search for relevant articles using keywords like "epigenetic", "stem cell", and "skeletal stem cell". Selection criteria included publication year, article title, abstract, Scopus ranking, and accessibility. Four articles were chosen as reference sources for the review. Recent research emphasizes cellular metabolism's role in regulating skeletal functions through skeletal stem cells (SSCs), crucial for skeletal health and potential regenerative therapies. Transcriptomic and epigenetic analysis of human SSCs reveal species-specific pathways. Metabolic pathways are vital for SSC selfrenewal and multipotency, with glycolysis being the primary energy source for human bone marrow stem cells. Aging affects bone cells and inherited epigenetic changes significantly influence cell fate. Recent studies identify Ptip as a key epigenetic regulator of glycolysis in SSCs, impacting growth plate activity.